2017
DOI: 10.1111/1744-7917.12477
|View full text |Cite
|
Sign up to set email alerts
|

Does drought stress modify the effects of plant‐growth promoting rhizobacteria on an aboveground chewing herbivore?

Abstract: Soil microbes have important effects on the interactions of plants with their environment, by promoting plant growth, inducing resistance to pests or by conferring tolerance to abiotic stress. However, their effects are variable and the factors responsible for this variation are mainly unknown. Our aim was to assess how drought stress modifies the effect of the nonpathogenic rhizobacterium Pseudomonas simiae WCS417r on plant growth and resistance against the generalist leaf-chewing caterpillar Mamestra brassic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
2
7
0
2
Order By: Relevance
“…Most studies of microbe-plant-herbivore interactions to date have focused on tripartite interactions within controlled environmental conditions. A few exceptions include studies that have considered abiotic factors like soil nutrients [169] or drought stress [170]. There is abundant evidence that abiotic factors, such as water or nutrient availability [171], solar radiation [172], and temperature [173] influence plant physiology and defensive traits.…”
Section: Conclusion and Perspectives For Future Researchmentioning
confidence: 99%
“…Most studies of microbe-plant-herbivore interactions to date have focused on tripartite interactions within controlled environmental conditions. A few exceptions include studies that have considered abiotic factors like soil nutrients [169] or drought stress [170]. There is abundant evidence that abiotic factors, such as water or nutrient availability [171], solar radiation [172], and temperature [173] influence plant physiology and defensive traits.…”
Section: Conclusion and Perspectives For Future Researchmentioning
confidence: 99%
“…Sterker nog, abiotische stressfactoren, zoals UV-straling en droogte, kunnen de afweer van het gewas tegen ziekten en plagen vaak juist verhogen (Demkura and Ballare 2012, Kruidhof et al 2012, Mewis et al 2012, de Bobadilla et al 2017, Escobar-Bravo et al 2017.…”
Section: Receptoren Voor Verrood Lichtunclassified
“…Fernandez de Bobadilla et al . () tested whether drought stress modulates the impact of a PGPR on resistance to a chewing herbivore. Interestingly, they showed that whereas drought itself had a strongly negative impact on herbivore performance, it did not alter the effect of PGPR on herbivore resistance.…”
Section: Direct and Indirect Effects Of Soil Microbial Communities Onmentioning
confidence: 99%
“…This has triggered an increased interest in how the (a)biotic environment modulates the effects of root symbionts on plant-herbivore interactions. Fernandez de Bobadilla et al (2017) tested whether drought stress modulates the impact of a PGPR on resistance to a chewing herbivore. Interestingly, they showed that whereas drought itself had a strongly negative impact on herbivore performance, it did not alter the effect of PGPR on herbivore resistance.…”
Section: Direct and Indirect Effects Of Soil Microbial Communities Onmentioning
confidence: 99%
See 1 more Smart Citation